Factor Analysis of Explanatory Variables in an Achievement Production Function - James L. Phelps (Educational Considerations, 2011)
Addendum: Combining explanatory variables into factors instead of using individual variables in an achievement production function is advocated in several of the articles in this special issue. The following is a brief overview of factor analysis explaining and illustrating the reasoning for this technique.
Keywords: Addendum; explanatory; variables; student; achievement; factor; analysis; concepts; characteristics